Effects of Physical Rehabilitation Integrated with Rhythmic Auditory Stimulation on Spatio-Temporal and Kinematic Parameters of Gait in Parkinson’s Disease - Pau, Massimiliano; Corona, Federica; Pili, Roberta; Casula, Carlo; Sors, Fabrizio; Agostini, Tiziano; Cossu, Giovanni; Guicciardi, Marco; Murgia, Mauro (Frontiers in Neurology, 2016)
Movement rehabilitation by means of physical therapy represents an essential tool in the management of gait disturbances induced by Parkinson’s disease (PD). In this context, the use of rhythmic auditory stimulation (RAS) has been proven useful in improving several spatio-temporal parameters, but concerning its effect on gait patterns, scarce information is available from a kinematic viewpoint. In this study, we used three-dimensional gait analysis based on optoelectronic stereophotogrammetry to investigate the effects of 5 weeks of supervised rehabilitation, which included gait training integrated with RAS on 26 individuals affected by PD (age 70.4 ± 11.1, Hoehn and Yahr 1–3). Gait kinematics was assessed before and at the end of the rehabilitation period and after a 3-month follow-up, using concise measures (Gait Profile Score and Gait Variable Score, GPS and GVS, respectively), which are able to describe the deviation from a physiologic gait pattern. The results confirm the effectiveness of gait training assisted by RAS in increasing speed and stride length, in regularizing cadence and correctly reweighting swing/stance phase duration. Moreover, an overall improvement of gait quality was observed, as demonstrated by the significant reduction of the GPS value, which was created mainly through significant decreases in the GVS score associated with the hip flexion–extension movement. Future research should focus on investigating kinematic details to better understand the mechanisms underlying gait disturbances in people with PD and the effects of RAS, with the aim of finding new or improving current rehabilitative treatments.